Morphometric analysis and lymph node yield in laparoscopic complete mesocolic excision performed by supervised trainees. Issue 11 (19th August 2014) - West, N P; Kennedy, R H; Magro, T; Luglio, G; Sala, S; Jenkins, J T; Quirke, P
Abstract: Background: Complete mesocolic excision with central vascular ligation (CME) produces an optimal colonic cancer specimen. The ability of expert laparoscopic surgeons to produce equivalent specimens is unknown. Methods: Fresh specimen photographs and clinicopathological data from patients undergoing laparoscopically assisted CME at St Mark's Hospital, Harrow, were submitted for independent pathological review. Surgery was performed by a mixture of consultant specialists and trainees under consultant specialist supervision, between February 2010 and July 2011. The planes of surgery were graded and tissue morphometry was performed using standard methods. The results were compared with published data from open CME and non-CME surgery. Results: In total, 69 patients were identified, and in 96 per cent resection was performed completely or partially by surgical trainees. Laparoscopic CME produced a similar specimen to open CME. The laparoscopic mesocolic plane resection rate was similar to that for open surgery (90 versus 88 per cent). The distance between the bowel wall and site of vascular division was similar for laparoscopic and open right-sided CME (92 versus 95 mm respectively). The corresponding values for left-sided CME were also similar (103 versus 107 mm). Compared with values from two non-CME series, laparoscopic CME had a higher mesocolic plane rate (90 versus 40 and 48 per cent), and resected more tissue between the bowel wall and the vascular division (right-sided: 92 versus 72 and 76 mm; left-sided: 103 versus 85 and 70 mm). The lymph node yield remained low following laparoscopic CME compared with open CME (median 18 versus 32; P < 0·001) and identical to that of non-CME surgery (median 18). Conclusion: Laparoscopic CME can be performed to the same standard as open surgery by supervised trainees. However, this did not increase the lymph node yield. Abstract : Feasible but nodal counts not up